Correlation study of renal function indices with diabetic peripheral neuropathy and diabetic retinopathy in T2DM patients with normal renal function - Zhang, Yue-Yang; Chen, Bing-Xue; Chen, Zhuang; Wan, Qin (Frontiers in Public Health, 2023)
The anticipation of diabetes-related complications remains a challenge for numerous T2DM patients, as there is presently no effective method for early prediction of these complications. This study aims to investigate the association between renal function-related indicators and the occurrence of peripheral neuropathy and retinopathy in individuals diagnosed with type 2 diabetes mellitus (T2DM) who currently have normal renal function.Methods: Patients with T2DM who met the criteria were selected from the MMC database and divided into diabetic peripheral neuropathy (DPN) and diabetic retinopathy (DR) groups, with a total of 859 and 487 patients included, respectively. Multivariate logistic regression was used to analyze the relationship between blood urea nitrogen(BUN), creatinine(Cr), uric acid(UA), urine albumin(ALB), albumin-to-creatinine ratio(ACR), estimated glomerular filtration rate(eGFR), and diabetic peripheral neuropathy and retinopathy.Spearman correlation analysis was used to determine the correlation between these indicators and peripheral neuropathy and retinopathy in diabetes.In a total of 221 patients diagnosed with DPN, we found positive correlation between the prevalence